Numerical Simulation of Main Negative Charge Area Parameters for Upward Negative Cloud-to-ground Lightning - Wang Yiru; Tan Yongbo; Zheng Tianxue; Yu Junhao; Li Chunsun; Liu Minzhi (应用气象学报)
Different types of lightning initiation condition are the focus of scientific research. The initiation of cloud lightning is competitive with self-sustaining uplink lightning. Based on the classical dipolar charge structure and the existing lightning discharge parameterization schemes, under the background of the classic dipolar charge structure, two-dimensional(2-D) high-resolution lightning discharge simulation experiments are carried out by adjusting the parameters of the main negative charge regions. Cloud charge structures which are beneficial to the onset of self-sustaining upward lightning are discussed. Results show that the part of the lightning at the beginning of the building has almost no bifurcation, and spreads straight toward the vertical direction. As the lightning continues developing, it gradually extends horizontally, and lightning channel branches gradually increase. Branches generally develop from bottom to top. The development of new branches in the front section of the main channel will hinder the development of lightning branches located to a certain extent. Branches at the same height may have a simultaneous developing trend. It can be inferred that this is related to the flat surface potential direction and the potential well in the charge region of the cloud. It is found that the higher the charge area is, the larger the charge density and distribution range the initial-self-sustaining uplink lightning needs. There speculates a threshold of the height of the main negative charge regions for the onset of upward lightning. When the negative charge region is higher than that, with the accumulation of charge in the main negative regions, the lightning will start in clouds instead of upward lightning. Only when the main negative area is lower than the threshold, the steady accumulation of electric charge will cause the flash originating. This may charge far away from the earth, and the cloud charge accumulation effects are greater than the increasing process of the electric field in the cloud for building sophisticated growth effects of electric field. As the main negative charge accumulates, the lightning starting conditions are firstly met in the cloud, initiating flashes in the clouds.